Usage of Agaricus and Pleurotus Spent Mushroom Composts as Growth Medium in Tomato Seedling Production - Caner YILMAZ; Ercan SIRÇA; Harun ÖZER; Aysun PEKŞEN (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
The effect of growth media prepared by adding of Agaricus bisporus (A) and Pleurotus ostreatus (P) spent mushroom compost into peat (PE) at different rates (25, 50, 75 and 100%) on tomato seedling growth and quality was examined in this study. In the study where peat is used as standard medium, seedling growth and quality parameters such as seedling length (cm), stem diameter (mm), root length (cm), leaf chlorophyll content (CCI), leaf area (cm2), total seedling dry weight (g), net assimilation rate (g cm-2 day-1) and relative growth rate (g g-1 day-1) were determined. Significant differences (p<0.05) were found among seedling growth media for tomato seedling quality parameters. The highest seedling length (25.5 cm), leaf chlorophyll content (11.13 CCI) and root length (15 cm) were obtained from control (peat) medium. The highest total seedling dry matter (0.24 g) was obtained from 25A+75PE medium, while the highest leaf area (42.97 cm2), net assimilation rate (44.33 g cm-2 day-1) and relative growth rate (6.14 g g-1 day-1) were determined in 75A+25PE growth medium. It was determined that tomato seedlings growth was better in the media added Agaricus bisporus (A) spent mushroom added compost than that in the media added Pleurotus spent mushroom compost.